Comparison of Pain Determination Between Celecoxib Tramadol in Third Molar Surgery: Comparative Pain Management - Ishaque, Eshnawar; Punjabi, Suneel Kumar; Qazi, Mahavosh; Hasan, Faiza; Memon, Zunair Akbar; Hassan, Sadia; Shams, Salman (Pakistan Journal of Health Sciences, 2024)
Selecting a reliable and well-tolerated analgesic to manage pain after surgical extraction of the third molar is still a difficult task. Objective: To compare the effect of celecoxib and tramadol in managing post-operative pain following third molar surgery. Methods: This cross-sectional research was conducted at the Department of Oral and Maxillofacial Surgery, Liaquat University of Medical and Health Sciences, Jamshoro. A total of 100 patients were included and equally allocated into two groups. Group-A received celecoxib, and Group-B received tramadol. Patients were assessed on follow-up visits on the 1st, 3rd, and 5th days post-surgery. Results: Data revealed a mean age of 28.72 ± 3.844 years for Group-A (celecoxib), consisting of 30 (60%) males and 20 (40%) females out of 50 respondents. Group-B (Tramadol) exhibited a mean age of 28.28 ±3.511 years, including 29 (58%) males and 21 (42%) females. Preoperational and 1st day post-operational pain scores were similar for celecoxib and tramadol (median 8), with no significant difference (p-value= 0.180 and p-value= 0.874). By the 3rd day, celecoxib patients reported significantly lower pain (median 3, IQR 2-4) compared to tramadol (median 5, IQR 4-6), p<0.001. On the 5th day, celecoxib also had significantly lower pain (median 0, IQR 0-1) than tramadol (median 1, IQR 0-2), p<0.001. Conclusions: The study concludes that celecoxib is more effective than tramadol in mitigating pain following third molar surgery.